Is bigger always better? The effect of body mass on physical characteristics of English academy rugby union players - Darrall-Jones, J. D.; Jones, B.; Till, K. (Journal of Australian Strength and Conditioning, 2018)
Differences in body mass do not explain the differences in physical characteristics in academy rugby union players, therefore practitioners should develop lean mass throughout the academy pathway, knowing it will not hinder development of strength, power, speed and fitness.